2008
DOI: 10.18433/j3x59g
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electronic Prescribing on the Professionalization of Community Pharmacists: A Qualitative Study of Pharmacists’ Perception

Abstract: -PURPOSE.To understand how the technology of electronic prescription (e-Rx) can transform the community pharmacist's role through its effects on professionalization. We define professionalization as a pharmaceutical practice centred on clinical activities and made possible by the establishment of professional pharmaceutical services. METHODS. We asked 12 community pharmacists who had participated in an e-Rx pilot project in the Canadian province of Quebec to fill out a qualitative survey on their experience. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…In addition, respondents did not perceive a large difference in terms of work processes or development of their professional role. A sample of Canadian pharmacists interviewed by Motulsky et al [10] identified more perceived change in terms of their professional role. However, in the Canadian system being evaluated, clinical information was given to patients; in the UK at present pharmacists do not receive any additional information over that received using the paper based system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, respondents did not perceive a large difference in terms of work processes or development of their professional role. A sample of Canadian pharmacists interviewed by Motulsky et al [10] identified more perceived change in terms of their professional role. However, in the Canadian system being evaluated, clinical information was given to patients; in the UK at present pharmacists do not receive any additional information over that received using the paper based system.…”
Section: Discussionmentioning
confidence: 99%
“…23 Many studies conducted in hospital settings have identified design flaws in HIT such as Computerized Physician Order Entry and Bar Code Assisted Medication Administration technology. 24 25 These design flaws have been linked to poor clinical outcomes which can easily lead to patient harm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to evaluate e‐prescribing from different aspects, including the attitudes of involved actors. As e‐prescribing has significant impact on the work of prescribers and pharmacists, respectively, most studies have focused on their attitudes and the effects on their work [3,4,7,12–25] . However, the transition to e‐prescribing also leads to significant changes for the patients, and have the potential to create benefits for them [8,12] .…”
Section: Introductionmentioning
confidence: 99%